1999
DOI: 10.1038/990101
|View full text |Cite
|
Sign up to set email alerts
|

Stable propagation of synchronous spiking in cortical neural networks

Abstract: The classical view of neural coding has emphasized the importance of information carried by the rate at which neurons discharge action potentials. More recent proposals that information may be carried by precise spike timing have been challenged by the assumption that these neurons operate in a noisy fashion--presumably reflecting fluctuations in synaptic input and, thus, incapable of transmitting signals with millisecond fidelity. Here we show that precisely synchronized action potentials can propagate within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
856
6
4

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 908 publications
(901 citation statements)
references
References 25 publications
35
856
6
4
Order By: Relevance
“…Precise spike times can lead to synchronous spike volleys in pools of neurons that can propagate from pool to pool in model 74 and in vitro 8 feedforward networks with a precision that depends on a number of physiological parameters. The sequential activation of multiple pools is referred to as a synfire chain (or as 'cortical songs' 75 ).…”
Section: Synfire Chains In Cortical Networkmentioning
confidence: 99%
“…Precise spike times can lead to synchronous spike volleys in pools of neurons that can propagate from pool to pool in model 74 and in vitro 8 feedforward networks with a precision that depends on a number of physiological parameters. The sequential activation of multiple pools is referred to as a synfire chain (or as 'cortical songs' 75 ).…”
Section: Synfire Chains In Cortical Networkmentioning
confidence: 99%
“…On the other hand, the duration of the cluster reveals the nature of propagation. For instance, nLFPs linked through a long series of time bins spanning dozens of milliseconds might reflect local synchronized activity, which propagates either in the form of waves (Prechtl, Cohen et al, 1997;Ermentrout and Kleinfeld, 2001) or synfire chains (Abeles, 1992;Diesmann, Gewaltig et al, 1999;Vogels and Abbott, 2005). In contrast, short-lived, but spatially extended clusters might represent tightly synchronized population spikes that can arise from reciprocally coupled neuronal populations (Traub, Whittington et al, 1996).…”
Section: Nlfp Clusters Reflect Precise Spatiotemporal Patterns Of Synmentioning
confidence: 99%
“…The distribution mechanism would be reflected in the ability of a local, synchronized group to trigger synchronization at distant sites in the network according to e.g. a synfire chain mechanism (Abeles, 1992;Diesmann, Gewaltig et al, 1999). Accordingly, an nLFP cluster would represent a cascade of topplings on the grid.…”
Section: Self-organized Criticality As a Homeostatic Principle Duringmentioning
confidence: 99%
“…A simple model for this type of processing is a feedforward network, in which each neuron in a given layer receives multiple synaptic inputs from neurons in the previous layer (Hebb, 1949;Abeles, 1991). The issue of propagation of spiking activity (firing rates or synchrony) in isolated feedforward networks (FFNs) has been addressed in several theoretical studies (Diesmann et al, 1999;Gerstner, 2000;Câteau and Fukai, 2001;Gewaltig et al, 2001;van Rossum et al, 2002;Litvak et al, 2003) and in experiments (Reyes, 2003). Numerical simulations of FFNs showed that excitation of the first group of neurons with a volley of near synchronous spikes may result in increased synchrony of the spike volley, which remains stable in subsequent layers (Diesmann et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The issue of propagation of spiking activity (firing rates or synchrony) in isolated feedforward networks (FFNs) has been addressed in several theoretical studies (Diesmann et al, 1999;Gerstner, 2000;Câteau and Fukai, 2001;Gewaltig et al, 2001;van Rossum et al, 2002;Litvak et al, 2003) and in experiments (Reyes, 2003). Numerical simulations of FFNs showed that excitation of the first group of neurons with a volley of near synchronous spikes may result in increased synchrony of the spike volley, which remains stable in subsequent layers (Diesmann et al, 1999). Thus, propagating synchrony in the FFN has been proposed as a model to explain the occurrence of task-related precise spike patterns observed in behaving primates (Abeles et al, 1993;Nicolelis et al, 1995;Riehle et al, 1997;Prut et al, 1998).…”
Section: Introductionmentioning
confidence: 99%